The Effect of 4/3/2 Technique on Iranian EFL Learners’ Speaking Fluency: The Moderating Role of Working Memory - Hossein Kargar Behbahani; Ehsan Namaziandost; Malihe YarAhmadi (Journal of Applied Linguistics)
This study examines the effect of the 4/3/2 technique on Iranian EFL learners' speaking fluency while also investigating the moderating role of working memory (WM). The study involved sixty EFL learners attending a language institute in Shiraz. The participants, aged 14 to 18, all shared Persian as their first language and had pre-intermediate proficiency in English. A pretest-posttest control group design was employed, with participants randomized into experimental and control groups. The 4/3/2 technique was implemented in the experimental group (EG), where learners performed a monologue task thrice, each under increasing time constraints. The control group (CG) received teacher-fronted sessions. Pre- and post-test measures of L2 oral fluency were collected using syllables per minute, with WM span assessed using a reading-span test. The results demonstrated a significant improvement in oral fluency in the EG compared to the CG. Furthermore, learners with higher WM demonstrated greater gains in fluency following the intervention. The findings suggest that the 4/3/2 technique holds promise for enhancing speaking fluency in EFL learners, with individual differences in WM span influencing the effectiveness of the intervention. These findings have implications for language teaching pedagogy and underscore the importance of considering cognitive factors in language learning interventions. The implications of this study extend to various stakeholders in language education, including language teachers, learners, materials developers, syllabus designers, policymakers, and teacher educators. By integrating these insights into language instruction and teacher training programs, educators and policymakers can work towards fostering more effective and engaging language learning experiences for learners